PROMOTING TOLERANCE AND CIVIC-MINDEDNESS WITHIN THE NATIONAL EDUCATION PROGRAM (International Educators Conference, 2025)
This article emphasizes the importance of social, moral, and ethical education in modern society, and particularly highlights the crucial role of instilling tolerance in youth. It analyzes the United Nations’ global “Sustainable Development Goals,” especially their principles related to human rights, peace, inclusion, and justice. It describes how these goals are being implemented in Uzbekistan in harmony with the Development Strategy of New Uzbekistan, and how this effort supports human dignity across seven priority areas.